Bruxismo em crianças: reações interna e externa dos sujeitos - Junia Maria Cheib Serra Negra (2006)
The present population-based epidemiological study assessed the habit of sleep bruxism among 2nd grade elementary schoolchildren at nine public and private schools in the city of Belo Horizonte, Brazil describe in three articles. The first article is an epidemiological transversal study and the others have a case-control design. A representative cross-sectional study was elaborated, composed of 652 children between the ages of 7 and 10 years. Paired 1:2 case-control studies were couched in the cross-sectional studies and carried out with 120 children with bruxism and 240 without the habit, all of whom were 8 years old and paired for gender and social vulnerability as well. The Social Vulnerability Index drawn up by the City of Belo Horizonte was employed for social classification. Patient charts were used for the clinical dental exam. A questionnaire was applied to parents in order to gather information on the presence of bruxism. The Child Stress Scale was used to measure stress levels. The neuroticism and responsibility scales of the Big Five Questionnaire for Children were applied and validated in order to assess personality traits. All instruments were tested in a pilot study. The internal consistency coefficients of the psychological scales (Cronbach's alpha) ranged from 0.70 to 0.90. Intra-examiner agreement presented a Kappa coefficient ranging from 0.80 to 0.91. The chi square test, McNemar test and multiple logistic regression were employed in the statistical analysis. In the cross-sectional study, there was a prevalence of nocturnal bruxism among 35.3% of the children, with no association between age, gender, social classification and the presence of the habit. In the adjusted model, it was observed that children with high levels of neuroticism (OR=1.9 CI 1.3-2.6) and responsibility (OR=2.2 CI 1.0-5.0) are twice as likely to present the habit of bruxism than those with low levels of these personality traits. Among the clinical dental criteria assessed in the one case-control study, the following were determined to be associated factors for triggering bruxism among children: worn canines (OR=2.3 CI 1.2-4.3) as well as the oral parafunctions of biting on objects (OR=2.0 CI 1.2-3.3) and clenching the teeth during waking hours (OR=2.3 CI 1.2-4.3). Regarding the psychological variables assessed in the other case-control study, it was determined that children with high levels of stress and psychological reactions to stress (OR=1.8 CI 1.1-2.9) and high levels of responsibility (OR=1.6 IC 1.0-2.5) are more likely to present the habit of nocturnal bruxism when compared to those that present low levels of these psychological variables. It was concluded that nocturnal bruxism in children is associated to personality characteristics. Children with the habit of bruxism are more likely to present psychological reactions to stress. Canine wear is one of the consequences associated to the presence of nocturnal bruxism among children, as are the oral parafunctions of biting on objects and clenching the teeth during waking hours. Integration measures between dentistry and psychology should be urged.